TEKNOLOGI PERTANIAN SEMI-ORGANIK PADA USAHATANI PADI: SUATU TINJAUAN DARI PERSPEKTIF ANALISIS INCREMENTAL BENEFIT-COST RATIO - Dudi Septiadi; Tajidan Tajidan; Wizatul Ika Wulandari (Fakultas Pertanian Universitas Mataram, 2023)
The evaluation of the viability of agriculture through the analysis of the R/C ratio is consideredinappropriate in the application of new technology. The analysis tool that is considered adequate is theincremental benefit-cost ratio (IBCR). The objective of the research was to determine the effect of theapplication of semi-organic agricultural technology on production and to research objective was todetermine the effect of semi-organic agricultural technology on production and achieve the researchobjectives, the research was carried out in 40 rice farming units in Pringgasela district, East LombokRegency. The survey was conducted in rice farms applying semi-organic agriculture technology andfarms applying non-organic agriculture technology during the planting season of 2022. In each group offarmers, there are 20 units of rice farming applied semi-organic technology, and 20 units applied semiorganic technology. Sampling used a quota sampling technique and data were analyzed using IBCR. Theresults showed that the application of semi-organic technology in rice farming had a negative impact onrice production and was not economical (not feasible) to be applied to rice farming in the tropics with anIBCR value of <1.00, due to the application of semi-organic agricultural technology to rice farmingnegative impact on rice production, as well as providing lower economic benefits compared to nonorganic farming technologies.